Experimental Study on Catalytic Oxidation of Toluene with Manganese Catalysts and Ozone at Low Temperature. Issue 4 (August 2019) - Guan, Jie; Wang, Di; Yuan, Hao; Guo, Yaoguang; Dai, Jue
Abstract: The single metal oxide catalyst of transition metal element Mn and the composite metal oxide catalysts of Mn-Co and Mn-Fe are prepared by impregnation method using activated carbon (AC) as carrier. The catalysts are characterized by x-ray diffraction (XRD), scanning electron microscope (SEM) and energy dispersive spectroscopy (EDS). The performance of the catalysts for catalytic ozonation of toluene is tested in a fixed bed tubular reactor. The results show that the activity of the single metal oxide catalyst of Mn is lower than that of the composite metal oxide catalysts of Mn-Co and Mn-Fe, and the activity of Mn-Co is higher than that of Mn-Fe. The catalytic efficiency of three catalysts is Mn/AC< Mn-Fe/AC> Mn-Co/AC. In this study, the factors influencing the degradation of toluene by catalytic ozonation are analyzed, and the mechanism is explored.